Faktor-Faktor Yang Mempengaruhi Minat Pelaku Usaha Kuliner Dalam Menggunakan Sertifikasi Halal : Studi Kasus Rumah Makan di Kota Medan - Fadiya Maysaroh Lubis; Mustapa Kamal Rokan; Budi Dharma (PT Maju Malaqbi Makkarana, 2023)
The aim of the following research is to determine the influence of understanding, cost, awareness and confidence factors on the interest of restaurant culinary entrepreneurs in Medan City in using halal certification. This research uses quantitative methods. Data was collected by distributing questionnaires with a purposive sampling technique to 78 respondents. The data used is Primary Data and Secondary Data. The data analysis tool used was multiple linear regression analysis using SPSS version 22. The variables understanding, costs, awareness and confidence contributed 91.7% and the remaining 8.3% was explained by other variables not included in this research. The results of the t test concluded that the variables understanding, costs, awareness and confidence had a positive and significant effect on the interest of restaurant culinary entrepreneurs in Medan City in using halal certification. From the results of the ANOVA test, the F-count was found to be 212,739 which is greater than the F-table (3.12), the conclusion is that understanding, costs, awareness and confidence simultaneously influence the interest of restaurant culinary entrepreneurs in Medan City in using halal certification.